Acceptability of Peanut Skins as a Natural Antioxidant in Flavored Coated Peanuts. Issue 10 (5th September 2018) - Christman, Lindsey M.; Dean, Lisa L.; Bueno Almeida, Camilla; Weissburg, Jacy R.
Abstract : Abstract: Peanut skins are a low‐value byproduct of the peanut processing industry. Following their removal during the preparation of common peanut products, they are either discarded or used as a minor component of animal feed. Studies have found peanuts skins to be rich in health promoting phenolic compounds and thus have potential as a functional food ingredient. The aim of this study was to evaluate a new product that included the encapsulated phenolic extract from peanut skins in a flavored coating for peanuts. The phenolic compounds were extracted from peanut skins and then encapsulated in 10.5% (w/w) maltodextrin in to reduce the bitter flavor. The encapsulated phenolic extract was added at varying concentrations to honey roast flavored and chili lime flavored coatings which were applied to roasted peanuts. The resulting total phenolic content and antioxidant potential of the coated peanuts were evaluated by the Folin‐Ciocalteu, DPPH, and β‐carotene bleaching assays. A best estimate sensory threshold for the peanut skin extract in the honey roasted and chili lime coating was found to be 12.8% (w/w) and 16.6% (w/w), respectively. The total phenolic content and antioxidant capacity for both the honey roasted and chili lime coated peanuts at their threshold was found to be significantly higher than control peanuts that did not contain peanut skins in the coating. The increased antioxidant activity and unaltered flavor profile at the sensory threshold levels of peanut skins demonstrated their potential as a functional food ingredient. Practical Application: The ability of polyphenols to act as antioxidants suggests that extracts of peanut skins containing polyphenols can be used as functional ingredients in new food products. The encapsulation of peanut skin extract in maltodextrin allowed for the incorporation of the extracts into flavored coatings for peanuts at levels high enough to increase the antioxidant activity without impacting sensory profiles. Utilization of this by‐product of the peanut can create an economic opportunity for the peanut industry.